Implementation of Patient Safety Goals in Hospitals: A Systematic Literature Review - Nur Inayah Rauf; Andi Mu'tiah Sari; Muhajrin Muhajrin (Pancasakti Journal Of Public Health Science And Research, 2025)
The provision of healthcare services to patients in hospitals carries the potential for incidents and injuries. Implementing the six patient safety goals serves as an organized framework to establish a culture, processes, behaviors, and environment that ensure safety for patients, healthcare providers, and the surrounding community. The aim of this study was to evaluate the implementation of the six patient safety goals in hospitals. This research employed a systematic literature review using the PRISMA technique (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). Literature searches were conducted using Google Scholar, with criteria for articles published between 2019 and 2024. The search terms included “Patient Safety Goals” AND “Hospitals.” Articles considered were original research discussing the six patient safety goals in full. A total of 2,250 articles were identified through Google Scholar, but only 12 articles met the inclusion criteria. Five articles specifically described the implementation of the six patient safety goals, while seven articles linked the goals to education, gender, work tenure, age, leadership, knowledge, work experience, and communication. In general, the implementation of patient safety goals adheres to the standards set by the Ministry of Health. However, improvements are needed in areas such as staff compliance and consistency, adequacy of facilities and infrastructure, as well as leadership support.